On anti-fuzzy subgroup - Gayen, Sudipta; Jha, Sripati; Singh, Manoranjan Kumar; Prasad, Ashish Kumar (Yugoslav Journal of Operations Research, 2021)
In this paper, efforts have been taken to generalise the notion of anti-fuzzy subgroup. Proposed definition was supported by graphical comparison with our previous result and suitably constructed examples. Based on the introduced definition, we derive not only some results of anti-fuzzy subgroup but also we redefine lower level set and lower level subgroup, and derive some essential theorems to study some algebraic characteristics. Further, a modified notion of lower level subgroup is given.